Left ventricular tamponade- pathophysiology determines the therapeutic approach: a case series. Issue 2 (11th December 2020) - Kumar, Barun; Kodliwadmath, Ashwin; Singh, Anupam; Upadhyay, Amar; Darbari, Anshuman; Duggal, Bhanu
Abstract: Background: Left ventricular (LV) tamponade is rare. LV tamponade can occur in cases of a loculated pericardial effusion overlying the LV and in cases of circumferential pericardial effusions in patients with severe pulmonary arterial hypertension (PAH). Both causes of LV tamponade share the common feature of not presenting with the classical features of cardiac tamponade. However, the therapeutic approach of the two is different. Case summary: Here, we report two cases of LV tamponade. The first patient was a case of post-mitral valve replacement who presented with loculated posterior pericardial effusion with LV tamponade. Due to the loculated and posterior nature of the effusion, his pericardial fluid was drained from the axilla by echocardiographic and fluoroscopic guidance. The second patient presented with features of severe PAH with a circumferential pericardial effusion and LV tamponade. Due to the circumferential nature of the effusion, the pericardiocentesis was performed from the subxiphoid route. Discussion: The pathophysiology of LV tamponade must be determined accurately before performing pericardiocentesis. Left ventricular tamponade in patients with severe PAH and non-loculated circumferential effusion can be drained from the subxiphoid route, while LV tamponade due to loculated effusion overlying LV must be drained by echocardiographic and fluoroscopic guidance from the axilla.